(untitled) (Research, Society and Development, 2024)
Anxiety is a psychological illness that causes a feeling of suffocation, causing limitations in daily occupations, which can be diagnosed with the help of DSM 5, the diagnostic manual for mental illnesses. In the CNS, neurotransmitters play an essential role in the defensive system that leaves the human being on alert or in expectation, and in anxiety this expectation is extrapolated, thus bringing the sensation of suffocation, mainly in GABA, the main neurotransmitter. The objective of this research was to analyze the herbal medicines of choice most used in the treatment of anxiety and verify forms of consumption, as well as their effectiveness in the treatment. This research was given the work methodology, a literature review in the scientific article model, over a period of 10 years, in the Scielo, Pubmed and Google academic databases. It is concluded that there is a range of herbal medicines, which are of great help in the treatment of anxiety, including plants from Brazil and others from abroad, but they must be used with care and in consultation with a health professional.